Social Media use as a Determinant of Knowledge Sharing Practices by Librarians in Tertiary Institutions in Lagos State, Nigeria - Obioma, Frances Uchechi (West African Journal of Open and Flexible Learning, 2016)
The proliferation of information and communication technology has had a significant influence on knowledge sharing practices in organizations. This has raised the consciousness of libraries to adopt the use of social media for the exchange of knowledge. Studies have indicated that knowledge sharing practices are not fully integrated in most libraries. Hence, this study investigated the extent to which social media is used to share knowledge in tertiary institutions in Lagos State, Nigeria. The survey research design was used for the study. The population of the study consisted of all 204 librarians in 21 tertiary institutions in Lagos State. Total enumeration was used for the study. Data collected were analysed using descriptive statistics for the research questions while linear regression was used to test the hypothesis. Findings revealed that social media use (B =.377, p<0.05) had a significant positive influence on knowledge sharing practices of librarians in tertiary institutions in Lagos State. In addition, the study showed that librarians mostly use brainstorming and verbal discussions for knowledge sharing among other knowledge sharing practices, which implied that knowledge sharing practices of librarians were low in the library. Findings also revealed that available social media tools were not fully utilized by librarians in tertiary institutions in Lagos State. The study concluded that social media use had a positive influence on knowledge sharing practices of librarians in tertiary institutions in Lagos State. The study recommended that knowledge sharing practices such as mentoring, community of practices, staff meetings and storytelling that were scarcely used to share knowledge should be encouraged in the library using diverse social media tools such as Pinterest, Ning, Flicker, Del.icio.us, Instagram and Social Bookmarking that were sparingly used in the library.